Effect of alternative postharvest control treatments on the storability of 'Golden Delicious' apples. (2nd April 2013) - Moscetti, Roberto; Carletti, Letizia; Monarca, Danilo; Cecchini, Massimo; Stella, Elisabetta; Massantini, Riccardo
Abstract Background Apples are subject to a high degree of fungal diseases, but the use of synthetic fungicides has been questioned because of public safety concerns, social rejection, and the development of resistance in pathogens. Thus, development of new postharvest treatments against apple fungal pathogens is necessary. Most studies have reported their effectiveness, but not all report the effects on the quality and storability of the fruit. In this study, the effects of physical (hot water), chemical (quercetin) and biological (yeast antagonist) microfungal control on the quality of 'Golden Delicious' apple during storage at 2 ± 0.5 °C, and 90 ± 2% of relative humidity, for 2 months were investigated and compared. Results Heat‐treated apples exhibited peel fruit damage (surface browning and internal breakdown disorders) and promoted ripening in the fruit. The quercetin caustic spray caused the development of peel chemical burn in all treated fruit. Both yeast antagonist and quercetin treatments did not affect the apple ripening process but stimulated an increase in ethylene production and in respiratory activity. Conclusion The data indicated that the effects on quality and storability were dependent on the method of treatment used, and antagonistic yeast was the best microfungal control because of it did not cause any disorders or negative effects on apple quality during storage. © 2013 Society of Chemical Industry